Iron-based catalyst, preparation method and application thereof, and preparation method of low-carbon olefin

By preparing a new iron-based catalyst with specific composition and structure, the problems of inactivation of iron-based catalysts and low olefin selectivity in Fischer-Tropsch synthesis are solved, and the effects of high catalytic activity and high olefin selectivity are achieved.

CN119318969AActive Publication Date: 2025-01-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310874884.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

Existing iron-based catalysts are prone to inactivate in Fischer-Tropsch synthesis and have low olefin selectivity, resulting in low reaction efficiency.

Method used

A novel iron-based catalyst is provided, including a support and active component, the general formula is Fe100AaNdbPd0.01bOx, A is selected from the group IVB, VIB and VIIB metal elements. Through specific preparation methods and calcining conditions, the catalyst surface Nd and The molar ratio of Pd is 100:4.5-7.5, which improves catalytic activity and olefin selectivity.

Benefits of technology

The catalytic activity of the catalyst and the selectivity of C2-C4 olefins, especially the proportion of C2-C4 olefins, enhance the efficiency of the FTO reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004342568130000161
    Figure BDA0004342568130000161
  • Figure BDA0004342568130000171
    Figure BDA0004342568130000171
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to an iron-based catalyst, a preparation method and application thereof and a preparation method of low-carbon olefin. The catalyst comprises a carrier and an active component, wherein the general formula of the active component is Fe < 100 > A Nd Pd < 0.01 b > O < x > according to an atomic ratio; a is selected from at least one of IVB group metal elements, VIB group metal elements and VIIB group metal elements; the value range of a is 2-20; the value range of b is 1-10, and x is the total number of oxygen atoms required by valence of each element in the catalyst; in terms of elements, the molar ratio of Nd to Pd on the surface of the catalyst is 100: (4.5-7.5). The catalyst provided by the invention is used in FTO reaction, not only has high catalytic activity, but also can obtain high C2 + olefin selectivity, especially C2-C4 olefin selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to an iron-based catalyst and a preparation method and application thereof, and a preparation method of light olefins. Background Art

[0002] Fischer-Tropsch synthesis is a complex reaction system in which CO and H2 (synthesis gas) generate hydrocarbons as the main products under the action of a catalyst. In general, it is a CO hydrogenation and carbon chain growth reaction. The method was invented by German scientists Frans Fischer and Hans Tropsch in 1923. The whole process includes reactions to generate alkanes and olefins, as well as methanation reactions, reactions to generate oxygen-containing organic compounds, and CO disproportionation reactions. Although all of the above reactions are possible, the probability of occurrence varies with different catalysts and operating conditions.

[0003] According to the classification of catalysts, Fischer-Tropsch catalysts can be divided into two categories: iron-based catalysts and cobalt-based catalysts. According to the operating conditions, they can be divided into high-temperature Fischer-Tropsch and low-temperature Fischer-Tropsch: low-temperature Fischer-Tropsch can use both cobalt-based catalysts and iron-based catalysts, and the products are mainly liquid to waxy straight-chain alkanes. High-temperature Fischer-Tropsch mostly uses iron-based catalysts, and the products are mainly light gasoline and diesel components, with some C2-C4 low-carbon olefins as by-products. CN1695804A introduces a precipitated iron-based catalyst for high-temperature Fischer-Tropsch synthesis.

[0004] Since the Fischer-Tropsch reaction is a highly exothermic reaction, although there have been some attempts to apply fixed beds to high-temperature Fischer-Tropsch production of light olefins, there are disadvantages such as difficulty in removing heat from the reactor, high temperatures, and easy deactivation of the catalyst. Fluidized beds can overcome these problems of fixed beds, but currently there is a problem of low olefin yields. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem that the iron-based catalyst in the prior art is easy to deactivate when used and the olefin selectivity is not high when used in the FTO reaction, and to provide a new iron-based catalyst and its preparation method and application. The catalyst is used in the FTO reaction, has high catalytic activity, and has high selectivity for C2-C4 olefins while also producing C2-C20 olefins with high chemical added value.

[0006] In order to achieve the above object, the present invention provides an iron-based catalyst in a first aspect, which comprises a carrier and an active component; wherein, in terms of atomic ratio, the general formula of the active component is Fe 100 A a Nd b Pd 0.01b O x; A is selected from at least one of Group IVB metal elements, Group VIB metal elements and Group VIIB metal elements; the value range of a is 2-20; the value range of b is 1-10, and x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst; calculated on an element basis, the molar ratio of Nd to Pd on the catalyst surface is 100:4.5-7.5.

[0007] A second aspect of the present invention provides a method for preparing an iron-based catalyst, the preparation method comprising:

[0008] (1) an aqueous solution containing a soluble Fe source and a precipitant are precipitated;

[0009] (2) taking the precipitate I obtained by precipitation in step (1), mixing and slurrying with an aqueous solution II containing a source A, an aqueous solution III containing a source Nd and a source Pd, and a carrier source, and adding a pH adjuster to obtain a slurry, followed by drying, optionally shaping, performing a first calcination in an oxygen-containing atmosphere, and performing a second calcination in an inert gas containing water vapor; wherein the water content in the oxygen-containing atmosphere is not greater than 1 ppm.

[0010] The third aspect of the present invention provides the use of the iron-based catalyst of the present invention in a FTO reaction.

[0011] A fourth aspect of the present invention provides a method for preparing low-carbon olefins, the method comprising: contacting synthesis gas with a catalyst, wherein the catalyst comprises the iron-based catalyst described in the present invention.

[0012] Through the above technical scheme, the catalyst of the present invention is used in the FTO reaction, which not only has high catalytic activity, but also can obtain high C2 + The selectivity of olefins, especially C2-C4 olefins. DETAILED DESCRIPTION

[0013] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0014] The first aspect of the present invention provides an iron-based catalyst, which comprises a carrier and an active component; wherein, in terms of atomic ratio, the general formula of the active component is Fe 100 A a Nd b Pd 0.01b O x; A is selected from at least one of Group IVB metal elements, Group VIB metal elements and Group VIIB metal elements; the value range of a is 2-20; the value range of b is 1-10, and x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst; calculated on an element basis, the molar ratio of Nd to Pd on the catalyst surface is 100:4.5-7.5.

[0015] The present invention provides a new iron-based catalyst, in which the various elements in the active components of the catalyst act synergistically with each other, and the molar ratio of Nd to Pd on the catalyst surface is controlled to be 100:4.5-7.5, which can significantly improve the catalytic activity of the catalyst. When the catalyst is used in the FTO reaction, it not only has high catalytic activity, but also can obtain high C2 + The selectivity of olefins, especially C2-C4 olefins.

[0016] In the present invention, it is understood that by the general formula Fe 100 A a Nd b Pd 0.01b O x The molar content ratio of Fe, A, Nd and Pd in ​​the active components can be obtained as 100:a:b:0.01b, which does not represent their actual molar content in the catalyst, for example, a=100 / molar content of Fe in the catalyst*molar content of A in the catalyst.

[0017] According to the present invention, in some embodiments, the carrier is selected from TiO2. The carrier and the active component in the catalyst of this embodiment have excellent synergistic effects, so that when the catalyst is used in the FTO reaction, it has high catalytic activity and selectivity for C2-C4 olefins.

[0018] According to the present invention, as long as the purpose of the present invention can be achieved, the content of the carrier and the active component in the catalyst is not particularly limited. In some embodiments, the mass ratio of the carrier to the active component is (50-80): (20-50), for example, 50:50, 60:40, 70:30, 80:20, or a range consisting of any two of the above ratios. When the catalyst of this embodiment is used in the FTO reaction, it has high catalytic activity and selectivity for C2-C4 olefins.

[0019] According to the present invention, in some embodiments, A is selected from Group VIB metal elements. When the catalyst of this embodiment is used in the FTO reaction, it has high catalytic activity and selectivity for C2-C4 olefins.

[0020] According to the present invention, in some preferred embodiments, A is at least one of Cr, Mo and W. When the catalyst of this embodiment is used in the FTO reaction, it has high catalytic activity and selectivity for C2-C4 olefins.

[0021] According to the present invention, in some more preferred embodiments, A is Cr. In the catalyst of this embodiment, each element in the active component, and the active component and the carrier have a more excellent synergistic effect. When the catalyst is used in the FTO reaction, it not only has high catalytic activity, but also can further increase C2 + The proportion of C2-C4 olefins in olefins.

[0022] According to the present invention, in some embodiments, the value range of a is 5-15, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or a range consisting of any two of the above values.

[0023] According to the present invention, in some embodiments, the value range of b is 2-8, for example, 2, 3, 4, 5, 6, 7, 8, or a range consisting of any two of the above values.

[0024] According to the present invention, as long as the purpose of the present invention can be achieved, the preparation method of the iron-based catalyst of the present invention is not particularly limited. Preferably, the second aspect of the present invention provides a preparation method of an iron-based catalyst, the preparation method comprising:

[0025] (1) an aqueous solution containing a soluble Fe source and a precipitant are precipitated;

[0026] (2) taking the precipitate I obtained by precipitation in step (1), mixing and slurrying with an aqueous solution II containing a source A, an aqueous solution III containing a source Nd and a source Pd, and a carrier source, and adding a pH adjuster to obtain a slurry, followed by drying, optionally shaping, performing a first calcination in an oxygen-containing atmosphere, and performing a second calcination in an inert gas containing water vapor; wherein the water content in the oxygen-containing atmosphere is not greater than 1 ppm.

[0027] In the present invention, a specific catalyst having a molar ratio of Nd to Pd on the catalyst surface of 100:4.5-7.5 can be prepared using the preparation method of the present invention, and a catalyst with specific lattice defects can be formed in the specific calcination environment of the first calcination and the second calcination of the present invention. When the catalyst is used in the FTO reaction, it not only has high catalytic activity, but also can further increase the selectivity of C2+ olefins, especially the selectivity of C2-C4 olefins among C2+ olefins.

[0028] According to the present invention, in some embodiments, the conditions for the first calcination include: a temperature of 550-750° C., preferably 580-720° C. When the catalyst prepared by this embodiment is used in the FTO reaction, it not only has high catalytic activity, but also can further increase C2 + Olefin selectivity, especially for C2 + Selectivity for C2-C4 olefins.

[0029] According to the present invention, in some embodiments, the conditions for the first calcination include: a time of 0.5-5 h, preferably 0.8-4.5 h.

[0030] According to the present invention, in some embodiments, during the second calcination, in the inert gas containing water vapor, the volume ratio of water vapor to inert gas is 1-5:100, for example, 1:100, 2:100, 3:100, 4:100, 5:100, or a range consisting of any two of the above ratios. The use of this embodiment can obtain a catalyst with specific lattice defects, which has high catalytic activity. When the catalyst is used in the FTO reaction, it not only has high catalytic activity, but also can further increase C2 + Olefin selectivity, especially for C2 + Selectivity for C2-C4 olefins.

[0031] According to the present invention, in some embodiments, the second calcination conditions include: a temperature of 580-800° C., preferably 600-760° C. When the catalyst obtained by adopting this embodiment is used in the FTO reaction, it has a higher catalyst activity and obtains a high target product C2 + The proportion of C2-C4 olefins in olefins.

[0032] According to the present invention, in some embodiments, the conditions for the second calcination include: a time of 0.5-5 h, preferably 0.8-4.5 h.

[0033] According to the present invention, as long as the purpose of the present invention can be achieved, the specific selection of the oxygen-containing atmosphere is not particularly limited, and can be oxygen and / or air. Based on cost considerations, in the present invention, the oxygen-containing atmosphere is selected as air, but the present invention is not limited to this.

[0034] According to the present invention, as long as the purpose of the present invention can be achieved, the selection of the inert gas is not particularly limited, for example, it can be nitrogen or argon.

[0035] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the pH adjuster is not particularly limited. In some embodiments, the addition of the pH adjuster makes the pH value of the slurry be 1-5.

[0036] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the pH adjuster is not particularly limited. In some embodiments, the pH adjuster is selected from at least one of ammonia water, ethylenediamine, triethanolamine, methylamine and ethylamine.

[0037] According to the present invention, in some embodiments, the solid content of the slurry is 15-45% by weight.

[0038] According to the present invention, in some embodiments, the beating conditions include: a temperature of 40-80° C., and optional addition of water.

[0039] According to the present invention, optionally adding water means that water may be added or not added during pulping as needed. In the present invention, water may be selectively added during pulping according to the desired solid content of the pulp.

[0040] According to the present invention, as long as the purpose of the present invention can be achieved, the method for precipitation in step (1) is not particularly limited. In some embodiments, in step (1), the precipitation method is co-current precipitation, that is, co-current precipitation of an aqueous solution containing a soluble Fe source and an aqueous solution containing a precipitant.

[0041] In the present invention, it is understood that in order to make the co-current precipitation proceed better, the precipitant in step (1) can be mixed with water before use.

[0042] According to the present invention, those skilled in the art can understand that precipitation is a fixed chemical reaction when the isoelectric point is reached, that is, those skilled in the art can select the amount of the precipitant according to the needs.

[0043] According to the present invention, as long as the purpose of the present invention can be achieved, the type of precipitant is not particularly limited. In some embodiments, the precipitant is selected from alkaline precipitants, preferably at least one of ammonia, KOH, NaOH, K2CO3 and KHCO3.

[0044] According to the present invention, the precipitate I obtained by precipitation in step (1) refers to the solid material after precipitation in step (1). Those skilled in the art can obtain the solid material in the material after precipitation in step (1) by conventional methods in the art. For example, the method for obtaining the precipitate I includes: performing solid-liquid separation and washing the material after precipitation in step (1) to obtain the precipitate I.

[0045] According to the present invention, there is no special limitation on the drying method when preparing the iron-based catalyst described in the present invention. For example, spray drying can be performed using a spray dryer; optional molding means that molding can be selected or not selected as needed, and when a spray dryer is used for drying, the solid matter in the slurry can be directly dried and molded into a microsphere, that is, molding is performed simultaneously during the drying process, and molding can be selected or not selected again as needed later.

[0046] According to the present invention, only the purpose of the present invention can be achieved, and the conditions when using a spray dryer for drying are not particularly limited, for example, the inlet temperature of the spray dryer is 300-350°C, and / or the outlet temperature is 170-230°C.

[0047] According to the present invention, the hot air medium during spray drying is not particularly limited, and can be, for example, an inert gas and / or air. Preferably, a mixed gas of air and an inert gas (such as nitrogen and / or argon) in a volume ratio of 1:(3-7) is used.

[0048] In the present invention, the aqueous solution containing Fe source refers to a solution prepared by dissolving Fe source in water; the aqueous solution II containing A source refers to a solution prepared by dissolving A source in water; the aqueous solution III containing Nd source and Pd source refers to a solution prepared by dissolving Nd source and Pd source in water; wherein the amount of water used in the aqueous solution containing Fe source, the aqueous solution II containing A source and the aqueous solution III containing Nd source and Pd source is not particularly limited, as long as it can dissolve the corresponding raw material sources and meet the requirements of the subsequent slurry.

[0049] According to the present invention, in some embodiments, the carrier source is selected from a sol solution of a carrier, preferably a TiO2 sol. The catalyst obtained by adopting the above embodiment has better catalytic performance.

[0050] According to the present invention, in some embodiments, the Fe source is selected from at least one of nitrate, citrate, chloride and nitrite of Fe.

[0051] According to the present invention, in some embodiments, the A source is selected from at least one of A's nitrate, oxide and chloride.

[0052] According to the present invention, in some embodiments, the Nd source includes nitrate and / or chloride of Nd.

[0053] According to the present invention, in some embodiments, the Pd source includes nitrate and / or chloride of Pd.

[0054] The third aspect of the present invention provides the use of the iron-based catalyst of the present invention in a FTO reaction.

[0055] The FTO reaction refers to the reaction of directly producing olefins from synthesis gas. In the present invention, the iron-based catalyst of the present invention is used in the FTO reaction, CO in the synthesis gas has a high conversion rate, and a high proportion of C2-C4 olefin products can be obtained.

[0056] A fourth aspect of the present invention provides a method for preparing low-carbon olefins, the method comprising: contacting synthesis gas with a catalyst, wherein the catalyst comprises the iron-based catalyst described in the present invention.

[0057] In the present invention, low-carbon olefins refer to C2-C4 olefins. When the iron-based catalyst of the present invention is used to prepare low-carbon olefins, CO has a high conversion rate and a high proportion of C2-C4 olefin products can be obtained.

[0058] When the iron-based catalyst of the present invention is used to prepare light olefins, it may be reduced or not before the reaction. Preferably, it is reduced first. More preferably, the reduction treatment conditions include: in H2 atmosphere, preferably at a temperature of 380-500°C, preferably at a pressure of normal pressure-8.0 MPa, preferably at a standard volume space velocity of 2000-12000 h -1 , the preferred reduction time is 4-500 hours.

[0059] According to a preferred embodiment of the present invention, the synthesis gas includes CO and H2, and preferably the volume ratio of CO to H2 is 1:2.5-4.5.

[0060] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the contact reaction are not particularly limited. According to a preferred embodiment of the present invention, the conditions of the contact reaction include: a reaction temperature of 300-380°C.

[0061] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: a reaction pressure of 0.5-8.0 MPa.

[0062] According to a preferred embodiment of the present invention, the contact reaction conditions include: a standard volume space velocity of 2000-12000 hours -1 .

[0063] The present invention will be described in detail below through examples. The water content in the air described in the following examples and comparative examples is less than 1 ppm.

[0064] The catalysts in the embodiment and the comparative example are respectively used in the reaction of preparing olefins from synthesis gas, wherein the catalyst is reduced by an in-situ reduction method, and after the reduction is completed, the process conditions are directly switched to synthesis reaction conditions in the reactor used for the reduction to start the reaction;

[0065] Reactor specifications: φ38 mm fluidized bed reactor;

[0066] Catalyst loading: 50 g;

[0067] The reduction conditions are: temperature 00°C, pressure 1.2 MPa, catalyst load (standard volume space velocity) 6000 h -1 , the reducing gas is H2, and the reducing time is 12 hours.

[0068] The synthesis conditions for preparing light olefins from syngas are: reaction temperature of 350°C, reaction pressure of 1.5 MPa, catalyst load (standard volume space velocity) of 6000 h -1 , the raw material ratio (molar) in the synthesis gas is CO / H2=1:4, and the reaction is run for 100 hours.

[0069] CO conversion rate = (CO reactor inlet volume - CO reactor outlet volume) / CO reactor inlet volume;

[0070] C2 + Olefin selectivity = C2 + Total carbon number of olefins / total carbon number of organic matter in the product;

[0071] C a -C b Olefins / C2 + Mass content = C a -C b Total carbon number of olefins / C2 + Total carbon number of hydrocarbons.

[0072] Example 1

[0073] Preparation of iron-based catalysts:

[0074] 404 g of Fe(NO3)3·9H2O was dissolved in water to prepare a 0.5 mol / L Fe element solution, and the solution was co-precipitated with 5 wt% ammonia water containing 3.5 mol NH3 and then separated, and washed three times with deionized water to obtain a fresh Fe(OH)3 precipitate I;

[0075] Take 7.6g of Cr2O3 and dissolve it in water to prepare a 0.5mol / L Cr aqueous solution II;

[0076] Take 17.5g of Nd(NO3)3·6H2O and 0.0004mol of 50mg / ml PdCl2 solution to make 0.5mol / L (Nd+0.01Pt) solution III.

[0077] A 40 wt% titanium sol containing 142 g of TiO2 was mixed with the precipitate I and solutions II and III, and stirred and slurried at 50°C. At the same time, the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 35% with water to obtain slurry III.

[0078] The slurry was spray dried to form, the inlet temperature of the sprayer was 350°C, the outlet temperature was 200°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray-dried material; the spray-dried material was first calcined at 650°C in an air atmosphere for 1 h, and then calcined at 600°C for 2 h in an atmosphere with a water vapor:nitrogen volume ratio of 3:100 to obtain an iron-based catalyst.

[0079] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Cr 10 NdPd 0.04 O x +60wt%TiO2.

[0080] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:5.7.

[0081] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0082] Example 2

[0083] Preparation of iron-based catalysts:

[0084] 404 g of Fe(NO3)3·9H2O was dissolved in water to prepare a 0.5 mol / L Fe element solution, and the solution was co-precipitated with 5 wt% ammonia water containing 3.5 mol NH3 and then separated, and washed three times with deionized water to obtain a fresh Fe(OH)3 precipitate I;

[0085] Take 3.8g of Cr2O3 and dissolve it in water to prepare a 0.5mol / L Cr aqueous solution II;

[0086] Take 17.5g of Nd(NO3)3·6H2O and 0.0004mol of 50mg / ml PdCl2 solution to make 0.5mol / L (Nd+0.01Pt) solution III.

[0087] A 40 wt% titanium sol containing 136.3 g of TiO2 was mixed with the precipitate I and solutions II and III, and stirred and slurried at 50°C. At the same time, the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 35% with water to obtain slurry III.

[0088] The slurry was spray dried to form, the inlet temperature of the sprayer was 320°C, the outlet temperature was 185°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray-dried material; the spray-dried material was first calcined at 630°C in an air atmosphere for 2 h, and then calcined at 600°C in an atmosphere with a water vapor:nitrogen volume ratio of 4:100 for 2 h to obtain an iron-based catalyst.

[0089] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Cr5Nd4Pd 0.04 O x +60wt%TiO2.

[0090] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:5.9.

[0091] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0092] Example 3

[0093] Preparation of iron-based catalysts:

[0094] 404 g of Fe(NO3)3·9H2O was dissolved in water to prepare a 0.5 mol / L Fe element solution, and the solution was co-precipitated with 5 wt% ammonia water containing 3.5 mol NH3 and then separated, and washed three times with deionized water to obtain a fresh Fe(OH)3 precipitate I;

[0095] Take 7.6g of Cr2O3 and dissolve it in water to prepare a 0.5mol / L Cr aqueous solution II;

[0096] Take 35g of Nd(NO3)3·6H2O and 0.0008mol of 50mg / ml PdCl2 solution to make 0.5mol / L (Nd+0.01Pt) solution III.

[0097] A 40 wt% titanium sol containing 152 g of TiO2 was mixed with the precipitate I and solutions II and III, and stirred and slurried at 50°C. At the same time, the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 30% with water to obtain slurry III.

[0098] The slurry was spray dried to form, the inlet temperature of the sprayer was 300°C, the outlet temperature was 170°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray-dried material; the spray-dried material was first calcined at 600°C in an air atmosphere for 3.5 hours, and then calcined at 750°C for 1 hour in an atmosphere with a water vapor:nitrogen volume ratio of 2:100 to obtain an iron-based catalyst.

[0099] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Cr 10 8P 0.08 O x +60wt%TiO2.

[0100] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:6.2.

[0101] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0102] Example 4

[0103] Preparation of iron-based catalysts:

[0104] Dissolve 404 g of Fe(NO3)3·9H2O in water to prepare 0.5 mol / L Fe element solution I;

[0105] Take 7.6g of Cr2O3 and dissolve it in water to prepare a 0.5mol / L Cr aqueous solution II;

[0106] Take 17.5g of Nd(NO3)3·6H2O and 0.0004mol of 50mg / ml PdCl2 solution to make 0.5mol / L (Nd+0.01Pt) solution III.

[0107] A 40 wt% titanium sol containing 142 g of TiO2 was mixed with solution I and solutions II and III and stirred at 50°C for slurrying. At the same time, the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 18% with water to obtain slurry III.

[0108] The slurry was spray dried to form, the inlet temperature of the sprayer was 350°C, the outlet temperature was 183°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray-dried material; the spray-dried material was first calcined at 650°C in an air atmosphere for 1 h, and then calcined at 600°C for 2 h in an atmosphere with a water vapor:nitrogen volume ratio of 3:100 to obtain an iron-based catalyst.

[0109] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Cr 10 NdPd 0.04 O x +60wt%TiO2.

[0110] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:4.5.

[0111] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0112] Example 5

[0113] Preparation of iron-based catalysts:

[0114] 404 g of Fe(NO3)3·9H2O was dissolved in water to prepare a 0.5 mol / L Fe element solution, and the solution was co-precipitated with 5 wt% ammonia water containing 3.5 mol NH3 and then separated, and washed three times with deionized water to obtain a fresh Fe(OH)3 precipitate I;

[0115] Take 7.6g of Cr2O3 and dissolve it in water to prepare a 0.5mol / L Cr aqueous solution II;

[0116] Take 17.5g of Nd(NO3)3·6H2O and 0.0004mol of 50mg / ml PdCl2 solution to make 0.5mol / L (Nd+0.01Pt) solution III.

[0117] A 40 wt% titanium sol containing 142 g of TiO2 was mixed with the precipitate I and solutions II and III, and stirred and slurried at 50°C. At the same time, the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 35% with water to obtain slurry III.

[0118] The slurry was spray dried to form, the inlet temperature of the sprayer was 350°C, the outlet temperature was 200°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray-dried material; the spray-dried material was first calcined at 650°C in an air atmosphere for 1 h, and then calcined at 600°C for 2 h in an atmosphere with a water vapor:nitrogen volume ratio of 6:100 to obtain an iron-based catalyst.

[0119] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Cr 10 NdPd 0.04 O x +60wt%TiO2.

[0120] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:7.5.

[0121] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0122] Example 6

[0123] Preparation of iron-based catalysts:

[0124] 404 g of Fe(NO3)3·9H2O was dissolved in water to prepare a 0.5 mol / L Fe element solution, and the solution was co-precipitated with 5 wt% ammonia water containing 3.5 mol NH3 and then separated, and washed three times with deionized water to obtain a fresh Fe(OH)3 precipitate I;

[0125] Take 7.6g of Cr2O3 and dissolve it in water to prepare a 0.5mol / L Cr aqueous solution II;

[0126] Take 17.5g of Nd(NO3)3·6H2O and 0.0004mol of 50mg / ml PdCl2 solution to make 0.5mol / L (Nd+0.01Pt) solution III.

[0127] 40 wt% silica sol containing 142 g of SiO2 was mixed with precipitate I and solutions II and III, stirred and slurried at 50°C, and the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 35% with water to obtain slurry III;

[0128] The slurry was spray dried to form, the inlet temperature of the sprayer was 350°C, the outlet temperature was 200°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray-dried material; the spray-dried material was first calcined at 650°C in an air atmosphere for 1 h, and then calcined at 600°C for 2 h in an atmosphere with a water vapor:nitrogen volume ratio of 3:100 to obtain an iron-based catalyst.

[0129] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Cr 10 NdPd 0.04 O x +60wt%SiO2.

[0130] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:4.4.

[0131] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0132] Example 7

[0133] Preparation of iron-based catalysts:

[0134] 404 g of Fe(NO3)3·9H2O was dissolved in water to prepare a 0.5 mol / L Fe element solution, and the solution was co-precipitated with 5 wt% ammonia water containing 3.5 mol NH3 and then separated, and washed three times with deionized water to obtain a fresh Fe(OH)3 precipitate I;

[0135] Take 17.65g of (NH4)6Mo7O 24 Dissolve in water to prepare 0.5 mol / L Mo aqueous solution II;

[0136] Take 17.5g of Nd(NO3)3·6H2O and 0.0004mol of 50mg / ml PdCl2 solution to prepare 0.5mol / L (Nd+0.01Pt) solution III;

[0137] A 40 wt% titanium sol containing 142 g of TiO2 was mixed with the precipitate I and solutions II and III, and stirred and slurried at 50°C. At the same time, the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 35% with water to obtain slurry III.

[0138] The slurry was spray dried to form, the inlet temperature of the sprayer was 350°C, the outlet temperature was 200°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray-dried material; the spray-dried material was first calcined at 650°C in an air atmosphere for 1 h, and then calcined at 600°C for 2 h in an atmosphere with a water vapor:nitrogen volume ratio of 3:100 to obtain an iron-based catalyst.

[0139] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Mo 10 NdPd 0.04 O x +60wt%TiO2.

[0140] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:6.7.

[0141] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0142] Comparative Example 1

[0143] Preparation of iron-based catalysts:

[0144] 404 g of Fe(NO3)3·9H2O was dissolved in water to prepare a 0.5 mol / L Fe element solution, and the solution was co-precipitated with 5 wt% ammonia water containing 3.5 mol NH3 and then separated, and washed three times with deionized water to obtain a fresh Fe(OH)3 precipitate I;

[0145] Take 7.6g of Cr2O3 and dissolve it in water to prepare a 0.5mol / L Cr aqueous solution II;

[0146] Take 17.5g of Nd(NO3)3·6H2O and 0.0004mol of 50mg / ml PdCl2 solution to make 0.5mol / L (Nd+0.01Pt) solution III.

[0147] A 40 wt% titanium sol containing 142 g of TiO2 was mixed with the precipitate I and solutions II and III, and stirred and slurried at 50°C. At the same time, the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 35% with water to obtain slurry III.

[0148] The slurry was spray dried to form, the inlet temperature of the sprayer was 350°C, the outlet temperature was 200°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray dried material; the spray dried material was calcined in an air atmosphere at 650°C for 1 hour, and then calcined in an air atmosphere at 600°C for 2 hours to obtain an iron-based catalyst.

[0149] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Cr 10 NdPd 0.04 O x +60wt%TiO2.

[0150] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:2.2.

[0151] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0152] Comparative Example 2

[0153] Preparation of iron-based catalysts:

[0154] 404 g of Fe(NO3)3·9H2O was dissolved in water to prepare a 0.5 mol / L Fe element solution, and the solution was co-precipitated with 5 wt% ammonia water containing 3.5 mol NH3 and then separated, and washed three times with deionized water to obtain a fresh Fe(OH)3 precipitate I;

[0155] Take 7.6g of Cr2O3 and dissolve it in water to prepare a 0.5mol / L Cr aqueous solution II;

[0156] Take 17.5g of Nd(NO3)3·6H2O and 0.0004mol of 50mg / ml PdCl2 solution to make 0.5mol / L (Nd+0.01Pt) solution III.

[0157] A 40 wt% titanium sol containing 142 g of TiO2 was mixed with the precipitate I and solutions II and III, and stirred and slurried at 50°C. At the same time, the pH value of the mixture was adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture was adjusted to 35% with water to obtain slurry III.

[0158] The slurry was spray dried to form, the inlet temperature of the sprayer was 350°C, the outlet temperature was 200°C, and the hot air medium of the sprayer was a mixture of air and nitrogen in a volume ratio of 1:5 to obtain a spray dried material; the spray dried material was first calcined at 650°C for 1 hour in an atmosphere of water vapor:nitrogen in a volume ratio of 3:100, and then continued to be calcined at 600°C for 2 hours to obtain an iron-based catalyst.

[0159] The composition of the obtained iron-based catalyst is: 40wt%Fe 100 Cr 10 NdPd 0.04 O x +60wt%TiO2.

[0160] XPS analysis showed that the molar ratio of Nd to Pd on the surface of the prepared catalyst was 100:8.1.

[0161] The catalyst was used in the reaction of preparing light olefins from synthesis gas. The results are shown in Table 1.

[0162] Table 1

[0163]

[0164]

[0165] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An iron-based catalyst, characterized in that The catalyst comprises a carrier and an active component; Wherein, in terms of atomic ratio, the general formula of the active component is Fe 100 A a Nd b Pd 0.01b O x ; A is selected from at least one of Group IVB metal elements, Group VIB metal elements and Group VIIB metal elements; a is in the range of 2-20; b is in the range of 1-10, and x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst; Calculated by element, the molar ratio of Nd to Pd on the catalyst surface is 100:4.5-7.

5.

2. The iron-based catalyst according to claim 1, wherein The carrier is selected from TiO2; and / or The mass ratio of the carrier to the active ingredient is (50-80): (20-50); and / or A is selected from Group VIB metal elements, preferably at least one of Cr, Mo and W, preferably Cr; and / or a is in the range of 5-15; and / or The value range of b is 2-8.

3. A method for preparing the iron-based catalyst according to claim 1 or 2, characterized in that: The preparation method comprises: (1) an aqueous solution containing an Fe source is precipitated with a precipitant; (2) taking the precipitate I obtained by precipitation in step (1), mixing and slurrying with an aqueous solution II containing a source A, an aqueous solution III containing a source Nd and a source Pd, and a carrier source, and adding a pH adjuster to obtain a slurry, followed by drying, optionally shaping, performing a first calcination in an oxygen-containing atmosphere, and performing a second calcination in an inert gas containing water vapor; wherein the water content in the oxygen-containing atmosphere is not greater than 1 ppm.

4. The preparation method according to claim 3, wherein The conditions for the first calcination include: a temperature of 550-750° C., preferably 580-720° C.; and / or a time of 0.5-5 h, preferably 0.8-4.5 h; and / or During the second roasting, the volume ratio of water vapor to inert gas in the water vapor-containing inert gas is 1-5:100; and / or The conditions for the second calcination include: a temperature of 580-800° C., preferably 600-760° C.; and / or a time of 0.5-5 h, preferably 0.8-4.5 h.

5. The preparation method according to claim 3 or 4, wherein The pH adjusting agent is added to make the pH value of the slurry 1-5; and / or The pH regulator is selected from at least one of aqueous ammonia, ethylenediamine, triethanolamine, methylamine and ethylamine; and / or The solid content of the slurry is 15-45% by weight; and / or The pulping conditions include: a temperature of 40-80° C. and optional addition of water.

6. The preparation method according to any one of claims 3 to 5, wherein: In step (1), the precipitation method is co-current precipitation; and / or The precipitant is selected from alkaline precipitants, preferably at least one of ammonia, KOH, NaOH, K2CO3 and KHCO3; and / or The method for obtaining precipitate I comprises: performing solid-liquid separation and washing on the material after precipitation in step (1) to obtain precipitate I.

7. The preparation method according to any one of claims 3 to 6, wherein: The carrier source is selected from a sol solution of a carrier, preferably a TiO2 sol; and / or The Fe source is selected from at least one of nitrate, citrate, chloride and nitrite of Fe; and / or The A source is selected from at least one of nitrates, oxides and chlorides of A; and / or The Nd source includes nitrate and / or chloride of Nd; and / or The Pd source includes Pd nitrate and / or Pd chloride.

8. Use of the iron-based catalyst according to claim 1 or 2 in FTO reaction.

9. A method for preparing light olefins, characterized in that: The preparation method comprises: The synthesis gas is contacted with the catalyst for reaction, wherein the catalyst comprises the iron-based catalyst according to claim 1 or 2; Preferably, the method further comprises reducing the catalyst before use, and preferably the reduction conditions include: under H2 atmosphere; and / or temperature of 380-500°C; and / or pressure of normal pressure-8.0MPa; and / or standard volume space velocity of 2000-12000 hours -1 ; and / or a reduction time of 4-500 hours.

10. The preparation method according to claim 9, wherein: The synthesis gas comprises CO and H2, preferably the volume ratio of CO to H2 is 1:2.5-4.5; and / or The contact reaction conditions include: reaction temperature 300-380°C; and / or reaction pressure 0.5-8.0 MPa; and / or standard volume space velocity 2000-12000 h -1 .

Citation Information

Patent Citations

  • Microsphere shaped iron based catalyst in use for Fischer-Tropsch synthesis under high temperature, and preparation method

    CN1695804A

  • Promoted carbide-based fischer-tropsch catalyst, method for its preparation and uses thereof

    CN101663090A

  • Iron-based catalyst for synthesizing low carbon olefin, and preparation method thereof

    CN104107699A

  • Preparation method of catalyst for preparing low-carbon olefin from synthesis gas

    CN112619651A

  • Sulfur-resistant denitration magnetic catalyst as well as preparation method and application thereof

    CN115228478A